Efficacy of Teprenone for Prevention of NSAID-Induced Gastrointestinal Injury: A Systematic Review and Meta-Analysis - Zhao, Chongxiang; Wang, Jingwu; Xiao, Qiang (Frontiers in Medicine, 2021)
Background: The study aimed to conduct a systematic review and meta-analysis comparing the efficacy of teprenone with control or other drugs for reducing the incidence of gastrointestinal (GI) adverse events in patients receiving long-term non-steroidal anti-inflammatory drugs (NSAIDs). Methods: Databases of PubMed, Embase, BioMed Central, CENTRAL, and Google Scholar were searched up to 10th November 2020 for randomized controlled trials (RCTs) comparing teprenone with control or other drugs. A random-effects model was used for the meta-analysis. Grading of Recommendations Assessment, Development, and Evaluation (GRADE) tool was used for assessing the certainty of evidence. Results: Seven RCTs were included. Six compared teprenone with control and one with famotidine. Meta-analysis indicated a statistically significant reduced risk of GI ulcers in patients receiving teprenone as compared to control after 12 weeks/3months (RR 0.37 95% CI 0.17, 0.18 I2=0% p=0.01). Pooled data of three studies indicated statistically significant reduction of GI symptoms in patients on teprenone as compared to control at 6 months and 12 months, but not at 3 months. Comparing teprenone with control, our analysis indicated non-significant but a tendency of better reduction in Modified Lanza Score (MLS) with teprenone. The RCT comparing teprenone to famotidine demonstrated better reduction of MLS with famotidine. The certainty of evidence-based on GRADE was deemed to be low. Conclusion: Low-quality evidence indicates a beneficial role of teprenone in preventing GI ulcers and symptoms in patients receiving long-term NSAIDs. Further high-quality RCTs comparing teprenone with placebo as well as other gastroprotective drugs are needed to strengthen current evidence.